Mapping and Improving Employee Engagement Driver Factors at PT XYZ - Mahardika, Bhaskara Putra; Gustomo, Aurik (Journal of Business and Management, 2015)
Abstract. PT. XYZ is a state-own oil and Gas Company of Indonesia. Founded in 13 September 2005, PT. XYZ is a company that runs an upstream business activity of oil and natural gas in Indonesia, covering exploration and exploitation. Based on PT. XYZ performance realization report, their employee engagement sector has scored 75% out of 100%. Based on that data, PT. XYZ left 25% room for improvement in Employee Engagement sector. The main point of this research is to mapping the employee engagement driver factor in the company in order to increase the employee engagement level of the company. In order to know which driver factor which have the most significant impact of the employee engagement, this research use a synthesis of employee engagement framework from ASTD, Gallup, and DDI. This research use questionnaire to gather the data and analyzed by SPSS. The result of this research was Job Fit became the most significant employee engagement driver factor in PT. XYZ. Based on that result, the suggestion plan for PT. XYZ was to apply the competency-based management and competency-based human resource to make a strong competency-based foundation in the company.Â Keywors : employee engagement, driver factor, employee performance, competency-based management, competency-based human resource.